THE USE OF ADVANCED MRI TECHNIQUES FOR THE EVALUATION OF SPINAL CORD AND PERIPHERAL NERVE DISORDERS - Abdullah Awadh M Alotaibi, Abdullah Mohammad Alajmi, Turky Nasser A Bin Ateeq,Muhannad Meshal Alotaibi, Abdulmohsen Maqboal Almutairi, Waleed Saeed Ali Al Hagawi, Mohammed Ahmed Koshan, Salah Ghobishan Alsohymi, ,; Emad Mshal Alotaibi, Abdulwahab Matar Almutairi, Ibrahem Hamad Alabdullah, Ziyad Mishal Al-Otaibi, Abdulmajed Nawaf N Alotabi, Nawaf Meshal Alotaibi, Abdullh Mesfer Saad Alosaimi, (Chelonian Research Foundation, 2022)
Extensive use of magnetic resonance imaging (MRI) has been made to identify pathological alterations in the central nervous system. MRI is, therefore, still largely underapplied in the assessment of the peripheral nervous system (PNS). The two perceived limitations of MRI that are typically to blame for this underutilization are: (1) the requirement for extremely high resolution in order to image the small structures within the peripheral nerves in order to visualize morphological changes; and (2) the absence of normative data in PNS MRI, which makes it challenging to interpret the data in a reliable manner. The most recent advancements in in vivo magnetic resonance imaging of human peripheral nerves are reviewed in this article. Its goal is to pinpoint the areas that have advanced and those that still need work. This study specifically discusses how MRI can be utilized to give objective, non-invasive biomarkers for the assessment of peripheral neuropathies, especially with a plethora of novel medications on the horizon. Despite the fact that there are numerous methods for identifying and monitoring PNS disorders, most of them focus on the distal peripheral nerves, which may be totally deteriorated when a patient attends their initial clinic appointment. Furthermore, the proximal nerves that are deeply entrenched in the tissue could not be accessible using these methods. An way to get around these issues would be peripheral nerve MRI. This analysis concludes with a clinical protocol at 3T that will enable high-resolution, high-contrast, quantitative MRI of the proximal peripheral nerves in order to answer the urgent clinical needs. Keywords: Charcot-Marie-Tooth disease, peripheral neuropathy, sciatic nerve, peripheral nervous system, and peripheral nerves.